Peptidic microarchitecture-trapped tumor vaccine combined with immune checkpoint inhibitor or PI3Kγ inhibitor can enhance immunogenicity and eradicate tumors - Pei Zhang; Ye Liu; Jie Tian; Jie Wang; Zhijie Wang; Hua Bai; Di Wang; Xiran He; Yang Du (Journal for ImmunoTherapy of Cancer)
Background With the rapid development of immune checkpoint inhibitors and neoantigen (NeoV)-based personalized tumor vaccines, tumor immunotherapy has shown promising therapeutic results. However, the limited efficacy of available tumor vaccines impedes the development of personalized tumor immunotherapy. In this study, we developed a novel tumor vaccine system and proposed combined therapeutic strategies for improving treatment effects.Methods We developed a novel tumor vaccine system comprising a newly synthesized peptidic microarchitecture (PMA) with high assembly efficacy. The PMA-trapped neoantigen vaccine was developed to codeliver tumor neoantigen and the Toll-like receptor 9 agonist CpG (NeoV), abbreviated as PMA-NeoV. A microfluidic chip was used to produce PMA particles in a uniform and precise manner. Vaccine effectiveness was investigated both in vitro and in vivo. The combined immunotherapeutic effect of PMA-NeoV with anti-programmed cell death ligand 1 antibody (aPD-L1) or with the phosphatidylinositol 3‑kinase γ (PI3Kγ) inhibitor IPI-549 was further tested in MC38 mouse tumor model.Results PMA-NeoV not only promoted codelivery of the tumor vaccine but also potentiated vaccine immunogenicity. Moreover, compared with free NeoV, PMA-NeoV significantly increased the number of tumor-infiltrating lymphocytes, promoted the neoantigen-specific systemic immune response, and suppressed murine colon MC38 tumor growth. Furthermore, PMA-NeoV increased the expression of programmed cell death receptor-1 on T lymphocytes, and in combination with aPD-L1 eradicated seven of eight MC38 tumors by rescuing exhausted T lymphocytes. Moreover, we combined the PMA-NeoV with the IPI-549, a molecular switch that controls immune suppression, and found that this combination significantly suppressed tumor growth and eradicated five of eight inoculated tumors, by switching suppressive macrophages to their active state and activating T cells to prime a robust tumor immune microenvironment.Conclusions We developed a tumor vaccine delivery system and presented a promising personalized tumor vaccine-based therapeutic regimen in which a tumor vaccine delivery system is combined with an aPD-L1 or PI3Kγ inhibitor to improve tumor immunotherapy outcomes.